2013
DOI: 10.1186/1479-5876-11-31
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miR-150 and miR-342 in plasma are novel potential biomarkers for acute myeloid leukemia

Abstract: BackgroundMicroRNAs (miRNAs) are small (19-22-nt) single-stranded noncoding RNA molecules whose deregulation of expression can contribute to human disease including the multistep processes of carcinogenesis in human. Circulating miRNAs are emerging biomarkers in many diseases and cancers such as type 2 diabetes, pulmonary disease, colorectal cancer, and gastric cancer among others; however, defining a plasma miRNA signature in acute myeloblastic leukemia (AML) that could serve as a biomarker for diagnosis or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(109 citation statements)
references
References 48 publications
5
101
1
1
Order By: Relevance
“…That study showed that miR‐342‐5p promotes inflammatory macrophage activation through an Akt1 and miR‐155‐dependent pathway during atherosclerosis (Wei et al ., 2013). In addition, two of the pattern A miRNAs (i.e., miR‐342 and miR‐146) have been associated with inflammation, proliferation, and cancer (Fayyad‐Kazan et al ., 2013). …”
Section: Discussionmentioning
confidence: 99%
“…That study showed that miR‐342‐5p promotes inflammatory macrophage activation through an Akt1 and miR‐155‐dependent pathway during atherosclerosis (Wei et al ., 2013). In addition, two of the pattern A miRNAs (i.e., miR‐342 and miR‐146) have been associated with inflammation, proliferation, and cancer (Fayyad‐Kazan et al ., 2013). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, miR-150 is significantly downregulated in the majority of acute myeloid leukemia (AML) cases, which is not associated with the DNA copy number changes, methylation or mutations (11). Furthermore, the results of a recent study revealed that the plasma expression of miR-150 was significantly downregulated in AML patients at diagnosis when compared with healthy controls; however, miR-150 plasma expression in complete remission AML patients resembled that of the healthy controls (19). Receiver operating characteristic curve analyses revealed that plasma miR-150 may serve as a valuable biomarker for the differentiation of AML patients from control individuals, with a sensitivity and specificity of 80 and 70%, respectively (19).…”
Section: Role Of Microrna-150 In Solid Tumors (Review)mentioning
confidence: 90%
“…Furthermore, the results of a recent study revealed that the plasma expression of miR-150 was significantly downregulated in AML patients at diagnosis when compared with healthy controls; however, miR-150 plasma expression in complete remission AML patients resembled that of the healthy controls (19). Receiver operating characteristic curve analyses revealed that plasma miR-150 may serve as a valuable biomarker for the differentiation of AML patients from control individuals, with a sensitivity and specificity of 80 and 70%, respectively (19). The expression signature of miR-150 in the plasma indicated that it may serve as a valuable diagnostic and potentially prognostic biomarker for human AML (19).…”
Section: Role Of Microrna-150 In Solid Tumors (Review)mentioning
confidence: 97%
See 1 more Smart Citation
“…Our previous studies showed that miR‐155 was significantly overexpressed in monoclonal B‐cell lymphocytosis (MBL) when compared with normal B cells and that miR‐155 overexpression in plasma is a predictor of poor response to therapy (Ferrajoli et al ., 2013). Similar studies have reported that miR‐150 and miR‐342 were significantly downregulated in the plasma of acute myeloid leukemia (AML) patients at diagnosis compared to healthy controls and that these microRNAs are candidate biomarkers and potential predictors of relapse in AML (Fayyad‐Kazan et al ., 2013). In addition, circulating miR‐192 has been found to be significantly downregulated in patients with chronic lymphocytic leukemia (CLL) compared with healthy individuals (Fathullahzadeh et al ., 2016).…”
Section: Circulating Mirnas As Biomarkersmentioning
confidence: 99%